Disparities in the Prevalence of Childhood Obesity-Related Comorbidities: A Systematic Review - Obita, George; Alkhatib, Ahmad (Frontiers in Public Health, 2022)
Background: Non-communicable diseases among children are serious consequence of childhood obesity. Little is, however, known about the disparities in childhood obesity comorbidities burden. This review describes the salient pattern of disparities in the prevalence of childhood obesity related non-communicable diseases and relevant inequalities, in both high- and low/medium-income countries. Method: A systematic literature search was performed in MEDLINE, EMBASE, CINAHL, PsycInfo, Scopus and Web of Science databases. Inclusion: age 2 -18 years; the prevalence or incidence of childhood obesity comorbidities reported; and published in English from January 2010 to date. No restrictions of the setting. The prevalence data was analyzed using range and median for sub-groups based on country’s development status, gender and geographical region. Results: Our search identified 6837 articles, out of which, we examined 145 full text and included 54 articles in the analysis. The median prevalence of childhood obesity related hypertension was 35.6% versus 12.7% among middle- and low-income countries compared to high income countries; 37.7% versus 32.9% among boys compared to girls; and 38.6%, 25.3% and 20.1% in Asia, South America, and Europe respectively. For metabolic syndrome, the median prevalence was 26.9% versus 5.5% among middle- and low-income countries compared to high income to countries; 55.2% versus 12.0% among boys compared to girls; and 40.3%, 25.8% and 7.7%, in South America, Asia and Europe, respectively. The prevalence of childhood obesity related non-alcoholic fatty liver disease was 47.5% versus 23% among middle- and low-income countries compared to high income countries; and 52.1%, 39.7% and 23.0% in Asia, South America, and Europe, respectively. The median prevalence of dyslipidemia was 43.5% versus 63% among middle- and low-income countries compared to high income countries; 55.2% versus 12.0% among boys compared to girls; and 73.7% and 49.2% in Australia and Europe, respectively. Conclusion: There are disparities in the prevalence of childhood obesity related hypertension, metabolic syndrome, and non-alcoholic fatty liver disease, with middle- and low-income countries, boys and Asian region having higher prevalence. Implementing targeted interventions for childhood obesity comorbidities should consider socio-economic disparities and strengthening of research surveillance methods for better understanding of non-communicable disease burden in the pediatric population.